ORGANIZATION OF WIKI-ORIENTED LEARNING ENVIRONMENT - Varchenko-Trocenko, Liliia O. (Educological discourse, 2014)
The article defines ways of using wiki-technology in the learning process, the advantages of wiki-technology to the educational environment, the structure of wiki-based learning environment.